RANCANG BANGUN APLIKASI ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA DEWI SINTA HOTEL AND RESTAURANT - NEGARA, I DEWA GEDE DIRGA; Tjandrarini, A.B.; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Dewi Sinta Hotel and Restaurant is a hotel in the Tanah Lot Temple area, Bali. Dewi Sinta Hotel and Restaurant is the first hotel in Tanah Lot Temple. This hotel has problem about service quality to customer satisfaction. Dewi Sinta Hotel and Restaurant need tool or application for analyze impact of service quality to customer satisfaction and then solve the problem. The application has quality service dimensions in customer satisfaction questionnaire. This application focus for analyze customer satisfaction questionnaire with multiple linear regression method. This application can result customer characteristic information and impact of service quality to customer satisfaction. The information will help managers for evaluation process about service quality in Dewi Sinta Hotel and Restaurant.